German unification and its impact on net savings - Horst Siebert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
The obsolete capital stock in eastern Germany has to be rebuilt. This will increase the capital demand in Germany for the next few years. In addition to the increased demand for capital, government transfers need to be financed. The macroeconomic accounting identity requires that net savings of the private sector and the government budget balance be equal to the current account. The DM150 billion swing in the current account from a surplus to a deficit between 1989 and 1991 must therefore find its counter expression in either net savings of the private sector or the budget deficit. If a narrow concept of the government budget deficit is used, there would be a government budget deficit of roughly 3-4 percent of GNP in the period 1991-1993, which is not too disturbing. In this case, however, net savings of the private sector, which would amount to 1- 2 percent of GNP, appear to be relatively low because the sums not included in the government budget deficit then show up as negative savings in the business sector. A case in point is the Treuhand's deficit. If a broader concept of the government budget deficit is applied, there would be a budget deficit reaching 7-8 percent of GNP in 1992 and 1993. In that case, savings of the private sector are artificially blown up because capital transfers to firms, for instance, the infusion of new capital into Treuhand firms, are part of savings in the private sector. The need to rebuild the capital stock in eastern Germany produces pressure for a higher longterm interest rate in Germany; this implies that the mark appreciates, which has already occurred. Only if severe policy mistakes are made will a risk premium on the German currency be required, which would imply a depreciation.
Keywords: 330; Sparen; Leistungsbilanz; Öffentliche Schulden; Zins; Wechselkurs; Nationale Einheit; Schock; Deutschland